Left Testicular Hypoplasia and Right Cryptorchid Testes Seminoma in a German Shepherd Dog - Shreemathi, Ravi; Ruthrakumar, Ravichandran; Vinayaga, Senthil Kumar Jawahar; Gopikrishnan, Duraisamy; Gopal, Kuppusamy; Selvaraju, Mani (The Indian Journal of Animal Reproduction, 2025)
This paper describes in detail a case of seminoma in an 8-year-old German Shepherd male dog with the history of dis tended abdomen and urinary incontinence and its successful surgical management.